2014
DOI: 10.3389/fnint.2014.00033
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing taste research: genetic and phenotypic predictors of bitter taste perception as a model

Abstract: Understanding the influence of taste perception on food choice has captured the interest of academics, industry, and the general public, the latter as evidenced by the extent of popular media coverage and use of the term supertaster. Supertasters are highly sensitive to the bitter tastant propylthiouracil (PROP) and its chemical relative phenylthiocarbamide. The well-researched differences in taste sensitivity to these bitter chemicals are partially controlled by variation in the TAS2R38 gene; however, this va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 31 publications
3
60
3
Order By: Relevance
“…Although many studies corroborated the original claim that FP density is a factor in PROP sensitivities 4,6,12,13 , there has been a small, but important contingency that has found evidence to refute it, reporting an inability to replicate the role 10,14,15,16 . Delwiche et al (2001) warned that the trend is highly variable; FP density does not uniformly account for differences in bitterness sensitivity across subjects, and was only demonstrable for subjects with at least a moderate sensitivity to PROP 7 .…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Although many studies corroborated the original claim that FP density is a factor in PROP sensitivities 4,6,12,13 , there has been a small, but important contingency that has found evidence to refute it, reporting an inability to replicate the role 10,14,15,16 . Delwiche et al (2001) warned that the trend is highly variable; FP density does not uniformly account for differences in bitterness sensitivity across subjects, and was only demonstrable for subjects with at least a moderate sensitivity to PROP 7 .…”
mentioning
confidence: 73%
“…The FP score data set was then used in the mixed model to assess the combined differences due to protocol (Figure 6), within-scorer variability and the interaction between the two. This model showed a significant difference in scoring when using the Miller & Reedy method compared to DPP (p-value <1 x 10 -6 ) with DPP leading to a higher count by 6.99 (SE = 0.99); 5.2% of the variability in the score was due to training, 25.9% due to scorer, and the remaining due to variability specific to the image 10 . Next, to generate data to determine within-scorer variability, a series of thirty images in random order were scored by 11 individuals.…”
Section: Scoring Fp Using the Denver Papillae Protocol Dichotomous Keymentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, it was suggested that higher density of FP may explain biological background of PROP super-tasting ability (Shahbake et al, 2005). However, the newest evaluating models revealed that predictors of taste sensitivity to PROP are age, sex, and haplotype rather than FP density (Garneau et al, 2014).…”
Section: Introductionmentioning
confidence: 99%